The Use Of Mediation As An Alternative Dispute Resolution In Oil And Gas Dispute - Sabela Gayo (IHSA Institute, 2022)
Regulation of oil and gas mining business activities in Indonesia has changed several times since the Dutch colonization until now the last with the transfer of BP Migas to Sksp Migas based on Presidential Regulation No. 95 of 2012 on the transfer of duties and functions of upstream oil and Gas business activities, which was followed by the issuance of the decree of the minister of energy and Mineral Resources No. 3135 Th. 2012 on the transfer of duties, functions and organizations in the implementation of upstream oil and Gas business activities and the decree of the minister of energy and Mineral Resources No. 3135 of 2012. In Law No. 22 of 2001 on oil and Gas and PP no. 35 years. 2004 on upstream oil and Gas business activities, there is no article that regulates the settlement of disputes in the event of a dispute between BP Migas and business entities and / or business forms. In practice, the dispute resolution clause is set forth in the agreement contract of the parties. Based on law no. 22 years. 2001, the parties are BP Migas with a business entity and / or permanent establishment. In the event of a dispute between BP Migas and a business entity, the law used is Indonesian law because both parties are legal entities established under Indonesian law and they are subject to Indonesian law. In the event of a dispute between a permanent establishment and BP Migas, the parties usually use the International Chamber of Commerce (ICC) for example a permanent establishment is a foreign company operating in Indonesia. The choice of settlement outside the court in oil and gas disputes can include mediation, abitrase and others referring to the dispute resolution on oil and gas the right choice in settlement is with the mediassi mechanism where there is a greeting Law No. 30 of 1999 on arbitration and Alternative Dispute Resolution.